KOMPETENSI GURU PENDIDIKAN EKONOMI TERHADAP IKLIM SEKOLAH - Herman man man (Jurnal Ilmu Pengetahuan Sosial, 2013)
This study aims to: (1) describe the relationship between the teacher competency economic subjects with school climate This research is a quantitative survey research design that uses a "cross sectional survey". This study also categorized descriptive correlational study using product moment correlation analysis. Subjects (population) studies are is a teacher of economic subjects in Makassar SMAN 48 teachers economic subjects. Data collection was performed using techniques, questionnaire, then the data were analyzed with descriptive analysis techniques and techniques Product Moment Correlation. Picture of teacher competence variables of economic subjects according to the perception of teachers of economic subjects in the high category with components of pedagogical competence, personal competence, social competence, and professional competence, is a component of teacher competency economic subjects in the National High School se Makassar.Overview variables according to teachers' perceptions of school climate conducive to the component category limitations, obstacles, passion, intimacy, keberjarakan, pressure on the results, encouragement, consideration and tolerance is a component of school climate in National High School se Makassar There is a significant correlation between teacher competence of economic subjects, the system reward / compensation to the school climate. The results of this study indicate that the better the relationship of teacher competence of economic subjects, the school would be more conducive climate.